Aberrant parasympathetic reactivity to acute psychosocial stress in male patients with schizophrenia spectrum disorders. (July 2018) - Andersen, Elizabeth H.; Lewis, Gregory F.; Belger, Aysenil
Highlights: Novel analytical approach used to characterize parasympathetic arousal regulation. Schizophrenia spectrum patients show aberrant autonomic flexibility during stress. Patients exhibit maladaptive basal autonomic activity relative to healthy controls. Atypical physiologic activity is associated with symptoms and cognitive deficits. Abstract: Autonomic dysfunction represents a core domain of the pathophysiology of schizophrenia spectrum disorders (SCZ), with aberrant physiologic arousal underlying maladaptive social and cognitive behaviors. Antagonistic parasympathetic and sympathetic systems support autonomic flexibility to appropriately regulate arousal and respond to environmental challenges, which can be modeled using physiologic measures. SCZ patients consistently show heightened basal stress, however, their parasympathetic reactivity to an acute psychosocial stressor is poorly understood. Heart period (HP-arousal), respiratory sinus arrhythmia (RSA-parasympathetic vagal activity), and their relationship were measured in SCZ patients ( n = 19) and healthy controls ( n = 20) at baseline and during psychosocial stress exposure. Parasympathetic vagal control of arousal, reflected in RSA-HP coupling, was assessed for the first time in SCZ. Patients demonstrated blunted physiologic reactivity (less change in heart period and respiratory sinus arrhythmia), a unique increase in respiratory sinus arrhythmia relative to baseline during recovery, and elevated arousal was associated with poor cognitive performance and greater positive symptoms. Arousal regulation was tightly controlled by parasympathetic activity in controls only, indicated by a strong association between changes in heart period and respiratory sinus arrhythmia. Results are the first to demonstrate maladaptive, inefficient parasympathetic arousal regulation (RSA-HP decoupling) in reaction to psychosocial stress in SCZ, representing an autonomic profile incompatible with appropriate social and emotional functioning.